Determinants of delinquency in the Peruvian banking and microfinance system, 2015–2020 - Quispe Mamani, Julio Cesar; Hancco Gomez, Miriam Serezade; Yapuchura Saico, Cristobal Rufino; Palomino, Juan Isidoro Gómez; Aguilar Pinto, Santotomas Licimaco; Vargas Espinoza, Jorge Luis; Chalco Vargas, Fredy Toribio; Maraza, Amira Carpio; Álvarez, Dominga Asunción Calcina; Quenta, Rolando Cáceres (Frontiers in Sociology, 2022)
Objective: The objective was to identify the variables that affect the delinquency rate in banking and microfinance institutions, between the periods 2015-2020, for which panel data models were used, considering the information registered in the banking and financial institutions to level of Peru. Method: The methodological design used is quantitative, not experimental, with a descriptive-correlational design, applying the analysis of data panel for each financial institution (Multiple Banking, Municipal Savings Banks), to observe the behavior over time for the same individuals. Results: It was determined that the behavior of the delinquency of microfinance institutions is having significant effects on the delinquency of loans, macroeconomic variables such as microeconomic variables do determine delinquency rates such as provisions, efficiency of analysts, financial income, liquidity in national currency, growth rate of Gross Domestic Product and the level of unemployment, both for banks and for municipal savings and credit banks, explaining the study variables in 84.30% in the banking system and in 48.95% in the financial system with respect to delinquency. Conclusions: Macroeconomic and microeconomic variables are determining factors for the level of delinquency in financial institutions.